Rapid and sensitive liquid chromatography-tandem mass spectrometric method for the quantitative determination of potentially harmful substance 5,5'-oxydimethylenebis (2-furfural) in traditional Chinese medicine injections - Qingce Zang; Yang Gao; Luojiao Huang; Jiuming He; Sheng Lin; Hongtao Jin; Ruiping Zhang; Zeper Abliz (Elsevier, 2018)
With the rapid development and wide application of traditional Chinese medicine injection (TCMI), a number of adverse events of some TCMIs have incessantly been reported and have drawn broad attention in recent years. Establishing effective and practical analytical methods for safety evaluation and quality control of TCMI can help to improve the safety of TCMIs in clinical applications. In this study, a sensitive and rapid high-performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS) method has been developed and validated for the quantitative determination of potentially harmful substance 5,5'-oxydimethylenebis (2-furfural, OMBF) in TCMI samples. Chromatographic separation was performed on a C18 reversed-phase column (150 mm × 2.1 mm, 5 µm) by gradient elution, using methanol-water containing 0.1% formic acid as mobile phase at the flow rate of 0.3 mL/min. MS/MS detection was performed on a triple quadrupole mass spectrometer with positive electrospray ionization in the multiple reaction-monitoring mode. The method was sensitive with a limit of quantification of 0.3 ng/mL and linear over the range of 0.3-30 ng/mL (r=0.9998). Intra- and inter-day precision for analyte was <9.52% RSD with recoveries in the range 88.0-109.67% at three concentration levels. The validated method was successfully applied to quantitatively determine the compound OMBF in TCMIs and glucose injections. Our study indicates that this method is simple, sensitive, practicable and reliable, and could be applied for safety evaluation and quality control of TCMIs and glucose injections. KEY WORDS: 5,5'-Oxydimethylenebis (2-furfural), LC-MS/MS, Quantitative analytical method, Traditional Chinese medicine injection, Quality control